(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The article proposes a new methodology for the knowledge of the electorate, coming from the field of psychology, which can serve as part of the inputs to define political communication strategies to win elections. By knowing the electorate better, one has a competitive advantage that can be decisive in winning an electoral campaign. The importance of voter knowledge is exemplified by describing the cases of the presidential elections in Colombia and Mexico in 2018. It is concluded that the cognitive window of the voter enables a better knowledge of the voters, and consequently, can help to improve the strategic sense in the struggle to occupy spaces of public representation in democratic regimes.